Community engagement in Malaysian higher education: an overview - Zakariya, Hafiz (2014)
The role of higher education in any country is indeed very important as it acts as a catalyst to foster a harmonious, productive society with robust economic growth. Higher education is of tremendous help to nation building through its ability to generate highly skilled workforce.This paper examines the state of community engagement in Malaysian higher education institutions. Community engagement in this paper refers to the collaboration ―between higher education institutions and their larger communities (local, regional/state, national, global)‖ (Driscoll, 2009, p. 6).